Mathematical Literacy and Transdisciplinarity: investigation of interrelationships Contemplated in the National Common Core Curriculum Base - Mario Jorge Nunes Costa; João Evangelista de Oliveira Neto; Maria José Costa dos Santos (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
This article theoretically investigates correspondences between the principles of Transdisciplinarity and the concept of Mathematical Literacy due to the need to reformulate the usual Mathematics teaching practices, which result in precarious learning for Brazilian students. Based on this investigation, in parallel, we present the results of a bibliographic mapping of national articles published between 2018 and 2021, interrelating ideas on Mathematics, Transdisciplinarity, and the National Curricular Common Base (BNCC in Portuguese), to identify Mathematical Literacy improvements. The results revealed that Mathematical Literacy can be transdisciplinary in BNCC as long as there is a development of skills such as self-management and teaching of Mathematics approaching contents in a transversal and multi-referential way. For future works, we suggest that studies deeply investigate aspects of Transdisciplinarity contained in the BNCC in the area of ​​Mathematics, as well as studies applying such aspects in pedagogical experiences of Mathematical Literacy.